Optimization Of Paid Advertising Strategies On The Meta Ads Platform To Increase Client Project Conversions At Belakang Kantor Marketing Agency - Yasa, Pri Yogha; Irwanto , Tito; Abi , Yudi Irawan (Utami Publisher, 2026)
Improving the effectiveness of digital advertising has become a critical concern in modern marketing, especially in service-based sectors such as healthcare, where communication must be both ethical and persuasive. This study investigates the implementation of paid advertising strategies on the Meta Ads platform to enhance conversion outcomes through direct messaging interactions between businesses and potential customers. The research was conducted at a digital marketing agency managing a circumcision service campaign in Cirebon, Indonesia. A descriptive quantitative method was applied by analyzing campaign performance data from two observation periods. The analysis focused on three strategic aspects: daily budget allocation, audience segmentation based on location and demographics, and variations in creative advertising content. The findings reveal that focused daily budget management can reduce cost per result and improve click-through rates without requiring additional overall expenditure. Audience segmentation with a narrower geographic target showed better conversion efficiency than broader targeting approaches. Moreover, advertisements using static images with clear calls to action outperformed video content in generating direct message responses from prospects. These results indicate that the combination of data-driven budgeting, precise audience targeting, and clear creative messaging can optimize advertising performance. This approach is particularly beneficial in sectors that rely on timely and trust-based interactions, such as healthcare services, where the conversion process depends on early and effective engagement.